2020
DOI: 10.1128/aac.01068-20
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Three Antiretroviral Regimens Initiated during Pregnancy: Clinical Experience in Rio de Janeiro

Abstract: Few studies have compared the clinical efficacy and adverse events of combined antiretroviral therapy (cART) regimens in pregnant women seeking obstetrical care. The objective of this study was to compare the efficacy (virus load response), adverse events and obstetrical and neonatal outcomes of three different regimens of cART in HIV-infected pregnant women initiating treatment in Rio de Janeiro, Brazil. This was a retrospective cohort study of cART- naïve pregnant women who initiated either ritonavir boosted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…We and Patel et al identified NNRTI and protease inhibitor alternatives with similar efficacy to dolutegravir, whereas other observational studies and randomized controlled trials have shown that INSTIs were superior to protease inhibitors or NNRTIs at achieving virologic suppression in pregnancy [3][4][5][6][7][8][9]17]. We suspect that the differences between those prior studies and our findings are a result of those studies using older and less potent anchors in the comparator groups and initiating ART late in pregnancy, leaving less time to achieve viral suppression prior to delivery.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We and Patel et al identified NNRTI and protease inhibitor alternatives with similar efficacy to dolutegravir, whereas other observational studies and randomized controlled trials have shown that INSTIs were superior to protease inhibitors or NNRTIs at achieving virologic suppression in pregnancy [3][4][5][6][7][8][9]17]. We suspect that the differences between those prior studies and our findings are a result of those studies using older and less potent anchors in the comparator groups and initiating ART late in pregnancy, leaving less time to achieve viral suppression prior to delivery.…”
Section: Discussionmentioning
confidence: 86%
“…Some INSTIs, in particular dolutegravir, also have a high genetic barrier to resistance. Several randomized controlled trials and observational studies have demonstrated superior virologic outcomes among pregnant women who received raltegravir compared with efavirenz, atazanavir/ritonavir, or lopinavir/ritonavir [3][4][5][6]. Three randomized controlled trials compared dolutegravir to efavirenz started in the second or third trimester and found that dolutegravir was superior at suppressing the viral load by delivery [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The group involved in the current study also took part in the follow‐up of this cohort prospectively. A detailed description of our institution's cohort has been published previously [13]. From October 2014 to October 2021, all pregnant women living with HIV who were referred for prenatal care to our centre, which is a national reference for PMTCT in Rio de Janeiro (one of the epicentres of the HIV epidemic in Brazil) and who met the study inclusion criteria were included.…”
Section: Methodsmentioning
confidence: 99%
“…5 RAL is safe for pregnant women, and the most common adverse event is the presence of abnormal hemoglobin values when compared with average values during pregnancy. 5,6 A study from Brazil 7 did not find differences in the frequency of preterm birth, low birth weight, small for gestational age, stillbirths, or perinatal mortality between neonates whose mothers received RAL and those whose mothers received other evaluated treatments, including efavirenz, lopinavir/ritonavir, or atazanavir/ ritonavir. RAL pharmacokinetics are highly variable, 8 with secondary peaks often seen in plasma concentrations versus time profiles, probably due to enterohepatic recycling or delayed absorption.…”
mentioning
confidence: 99%